Charismatic Leadership and Rhetorical Competence: An Analysis of Steve Jobs's Rhetoric. (April 2014) - Heracleous, Loizos; Klaering, Laura Alexa
One of the primary ways leaders influence others is through their rhetoric. Despite the clear link between charismatic leadership and rhetorical competence, empirical studies of this link in the management field remain sparse. We thus do not have a clear sense of the nature of the rhetoric of charismatic leaders and whether or how they alter their rhetoric in different situations. We conduct an in-depth case study of the rhetoric of the late Steve Jobs, an acknowledged charismatic leader, to expand our understanding of the fundamental link between charismatic leadership and rhetorical competence. We found not only an integration of customization to different audiences and situations but also continuity in central themes in different rhetorical contexts, which may be a key attribute of the competence of charismatic leaders. We also find that customized rhetorical strategies are influenced by the leader's perceived ethos (credibility) in the respective situations, which in turn influences the extent of logos (appeal to logic) and pathos (appeal to emotions) employed.